Intelligent power system protection data management - Hanzah, Nurulhuda Hanzah (2013)
The Power Flow is the most important issue to ensure an efficient yet affordable system. To maintain a low failure electrical breakdown or blackout analysis of faults leads to appropriate protection settings which can be computed in order to select suitable fuse, circuit breaker size and type of relay. The studies and detection of these faults is necessary to ensure that the reliability and stability of the power system do not suffer a decrement as a result of a critical event such a fault. This project will analyze a power systems under fault conditions.